1978
DOI: 10.1116/1.569571
|View full text |Cite
|
Sign up to set email alerts
|

Significance of negative ion formation in sputtering and SIMS analysis

Abstract: An unexpected substrate etching phenomenon during the sputtering of certain intermetallic compounds has been found to be caused by a large flux of negative metal ions from the sputtering target. The substrates directly under the target in a diode geometry are etched (eroded) rather than coated with a film. The occurrence of this substrate etching has been correlated with negative ion yields measured by secondary ion mass spectroscopy (SIMS). We find a high yield of negative metal ions from several intermetalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…3, i.e., smooth surface roughness was observed for the films grown with oxygen in the sputtering ambient. Even though the I − EA could not be an absolute standard value of resputtering, the I − EA value of ITO was about 4.36 eV when the value was gathered from the previous studies [22][23][24], which signifies that the resputtering effect might not be such a serious problem in ITO system. From these points of view, even though resputtering might have partly contribute to ITO system, it has not predominantly affected the surface characteristics of ITO.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…3, i.e., smooth surface roughness was observed for the films grown with oxygen in the sputtering ambient. Even though the I − EA could not be an absolute standard value of resputtering, the I − EA value of ITO was about 4.36 eV when the value was gathered from the previous studies [22][23][24], which signifies that the resputtering effect might not be such a serious problem in ITO system. From these points of view, even though resputtering might have partly contribute to ITO system, it has not predominantly affected the surface characteristics of ITO.…”
Section: Methodsmentioning
confidence: 94%
“…3, a very rough surface was observed in the (400) Concerning the momentum transfer of oxygen, the resputtering effect has been studied in sputtering-assisted oxide thin film growth, in which negative oxygen ions are frequently formed [20][21][22][23][24][25][26]. Cuomo et al suggested that if the value of I − EA (I: ionization potential, EA: electron affinity) were less than 3.4 eV, they predicted a negative ion formation, and the presence of resputtering effects [22,23]. A subsequent study by Kester et al [24] showed that the negative ion resputtering became stronger as the I − EA value decreased.…”
Section: Methodsmentioning
confidence: 99%
“…We use a similar argument as suggested by Cuomo et al 24 in describing negative ion formation and backsputtering. The envisaged barrier is the difference between the metal ionization potential IP M and the electron affinity EA O of the oxygen atom as listed in Table I.…”
mentioning
confidence: 82%
“…In subsequent experiments with other materials, the same group could confirm this general trend but not the value (3.5 eV) for the limit. 34 Kester and Messier 35 found that even the trend may be overlapped by the influence of other parameters, e.g., the structure and stoichiometry of the sputtered material. We have applied this model to our data assuming a completely oxidized target.…”
Section: Model Comparison Of the Overall O 2 Fluxmentioning
confidence: 97%